STUDY OF MINDANAO EDDY AND HALMAHERA EDDY - (NIM 22405001), MARTONO
This research is conducted to study the characteristics and variability of Mindanao and Halmahera Eddies at seasonal and interannual time scales under normal, El Nino, and La Nina conditions. A three-D baroclinic hydrodinamics model used in this research is COHERENS (A Coupled Hydrodynamical-Ecological Model for Regional and Shelf Seas) which was developed by Luyten, et al., (1999). Bathimetry, water temperature, salinity, wind, air temperature, rain fall, evaporation, cloud cover, and air pressure are used as input data. The results show that the variability of Mindanao Eddy and Halmahera Eddy is influenced by seasonal wind, El Nino and La Nina conditions. Under normal condition, during west monsoon the center of Halmahera Eddy is located farthest south around 6,3o N and 128,5o E, during first transition season it moves northward around 7o N and 128,5o E, during east monsoon it moves further northward around 7,7o N and 128,5o E, and during second transition monsoon it moves again southward around 7o N and 128,5o E. In general, the diameter and velocity of the Mindanao and Halmahera Eddies are smaller during El Nino, and greater during La Nina than normal condition.